cblE type of homocystinuria due to methionine synthase reductase deficiency: functional correction by minigene expression - Zavadáková, Petra; Fowler, Brian; Suormala, Terttu; Novotna, Zorka; Mueller, Peter; Hennermann, Julia B; Zeman, Jirí; Vilaseca, M Antonia; Vilarinho, Laura; Gutsche, Sven; Wilichowski, Ekkehard; Horneff, Gerd; et al. (Human mutation, 2005)
The cblE type of homocystinuria is a rare autosomal recessive disorder caused by impaired reductive activation of methionine synthase. Although earlier biochemical studies proposed that the methionine synthase enzyme might be activated by two different reducing systems, mutations were reported in only the methionine synthase reductase gene (MTRR) in cblE patients. The pathogenicity of MTRR mutations, however, has not yet been tested functionally. We report on nine patients of European origin affected by the cblE type of homocystinuria. They presented between 2 weeks and 3 years of age (median age 4 weeks) with anemia, which was macrocytic in only three patients, and with neurological involvement in all but two cases. Bone marrow examination performed in seven patients showed megaloblastic changes in all but one of them. All patients exhibited moderate to severe hyperhomocysteinemia (median plasma total homocysteine [Hcy] 92 mumol/L, range 44-169), while clearly reduced methionine was observed only in four cases. Pathogenic mutations were identified in both parental alleles of the MTRR gene in all patients. Five known (c.903+469T>C, c.1361C>T, c.1459G>A, c.1557-4_1557+3del7, and c.1622_1623dupTA) and three novel mutations (c.7A>T, c.1573C>T, and c.1953-6_1953-2del5) were detected. Importantly, transfection of fibroblasts of cblE patients with a wild-type MTRR minigene expression construct resulted in a significant approximately four-fold increase of methionine synthesis, indicating correction of the enzyme defect. Our study shows a link between a milder predominantly hematological presentation and homozygosity for the c.1361C>T mutation, but no other obvious genotype-phenotype correlation. The identification of mutations in the MTRR gene, together with restoration of methionine synthesis following MTRR minigene expression in cblE cells confirms that this disease is caused by defects in the MTRR gene.
Keywords: Sequence Deletion; kyselina listová; bodová mutace; transfekce; Cell Line, Transformed; transformované buněčné linie; Mutation, Missense; DNA Mutational Analysis; hydroxokobalamin; sekvenční delece; haplotypy; polymerázová řetězová reakce; fibroblasty; Homocystinuria; Hydroxocobalamin; 5-methyltetrahydrofoláthomocystein-S-methyltransferasa; missense mutace; Recombinant Fusion Proteins; Genes, Synthetic; Fibroblasts; polymorfismus genetický; nesmyslný kodon; Transfection; Brain; genetická terapie; 5-Methyltetrahydrofolate-Homocysteine S-Methyltransferase; běloši; Betaine; Haplotypes; Folic Acid; rekombinantní fúzní proteiny; Genetic Therapy; Polymorphism, Genetic; White People; mutační analýza DNA; ferredoxin-NADP-reduktasa; Amino Acid Substitution; Point Mutation; homocystein; lidé; Humans; substituce aminokyselin; Genetic Complementation Test; betain; testy genetické komplementace; mozek; Codon, Nonsense; polymorfismus délky restrikčních fragmentů; Polymerase Chain Reaction; homocystinurie; syntetické geny; Homocysteine; Polymorphism, Restriction Fragment Length; Ferredoxin-NADP Reductase